2013
DOI: 10.5152/jtgga.2013.49225
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the afterloaded external guidance embryo transfer technique on pregnancy rates in single embryo transfer cycles

Abstract: Objective: To investigate effect of the afterloaded external guidance embryo transfer technique on pregnancy rates in single embryo transfer intracytoplasmic sperm injection (ICSI) cycles. Material and Methods:This retrospective study was performed at the Dr. Zekai Tahir Burak Women's Health Research and Education Hospital. Three hundred and thirteen women who underwent ICSI were included in the study. Subjects were categorized according to the embryo transfer technique; Group 1 (n: 232): easy transfer with a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…Some existing studies have shown that the type of ET used can have as significant an effect on pregnancy rates in IVF-ICSI cycles as clinical and embryologic features, but different results have been reported ( 5 , 6 , 7 , 8 , 9 , 10 ) . In particular, Yılmaz et al ( 5 ) retrospectively compared the effects of undergoing easy, moderate, or difficult ET on CPR in 313 IVF-ICSI cycles and found that difficult ET was associated with lower CPR but with no statistically significant difference. Elsewhere, Burke et al ( 14 ) compared 159 cases of fresh ET with 46 frozen ETs and found that the technique and type of catheter used did not affect CPR.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Some existing studies have shown that the type of ET used can have as significant an effect on pregnancy rates in IVF-ICSI cycles as clinical and embryologic features, but different results have been reported ( 5 , 6 , 7 , 8 , 9 , 10 ) . In particular, Yılmaz et al ( 5 ) retrospectively compared the effects of undergoing easy, moderate, or difficult ET on CPR in 313 IVF-ICSI cycles and found that difficult ET was associated with lower CPR but with no statistically significant difference. Elsewhere, Burke et al ( 14 ) compared 159 cases of fresh ET with 46 frozen ETs and found that the technique and type of catheter used did not affect CPR.…”
Section: Discussionmentioning
confidence: 99%
“…Despite all the developments in assisted reproductive technology (ART) since the first live birth following in vitro fertilization (IVF) in 1978, pregnancy rates have remained at around 35-45% ( 1 , 2 , 3 , 4 ) . In ART cycles, the method of embryo transfer (ET) is important to clinical pregnancy success in addition to features such as age, the endometrial receptivity of the infertile woman, and embryo quality ( 5 , 6 , 7 , 8 ) . It has been claimed that faulty ET is responsible for 25-30% of failed implantations, relating either to the catheter application technique or the experience of the physician performing the ET procedure ( 9 , 10 , 11 , 12 ) .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Surrogacy, oocyte or sperm donation, human cloning, and the commercial purchase and sale of human reproductive products are legally prohibited and restricted in Türkiye (8). Many factors can affect the success of ART, such as the age of the infertile couple, embryo quality, endometrial receptivity, and embryo transfer technique (9)(10)(11)(12). In this study, we aimed to evaluate the demographic and stimulation characteristics, treatment results, and pregnancy outcomes of infertile couples who applied to our assisted reproductive technology (ART) center between January 2012 and December 2017.…”
mentioning
confidence: 99%